A high-sensitivity hydrogen gas sensor based on carbon nanotubes fabricated on SiO2 substrate - Ahmad M. Al-Diabat (Taylor & Francis Group, 2021)
In this study, an inexpensive simple method for the fabrication of efficient hydrogen (H2) gas sensor based on carbon nanotubes (CNTs) was presented. The CNTs were synthesized using microwave oven and deposited onto SiO2 substrate by a dielectrophoretic method. The as-grown CNTs showed an n-type behavior because CNTs possess the characters of both metallic and semiconductor when placed between the two electrodes, meanwhile, the current was directed mostly by metallic tubes. Upon exposure to H2 gas at room temperature, the CNTs exhibited high sensitivity up to 315% at 140 ppm H2, and relatively good sensitivity of 40% at a very low H2 gas concentration of 20 ppm. To the best of our knowledge, this is the first work involving the fabrication of CNTs for detecting a low H2 gas concentration of 20 ppm at RT with high sensitivity comparing with other previous studies.